KONTRIBUSI LINGKUNGAN SEKOLAH TERHADAP PERILAKU DISIPLIN SISWA KELAS VIII SMP RAHMATAN LIL’ALAMIN INTERNATIONAL ISLAMIC BOARDING SCHOOL SEMESTER GENAP TAHUN AJARAN 2025/2026 - Nayla Rahma Oktaviani; Linda Fitria; Ridho Rismi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the contribution of the school environment to the disciplinary behavior of eighth-grade female students at SMP Rahmatan Lil’Alamin International Islamic Boarding School in the even semester of the 2025/2026 academic year. This research employed a quantitative correlational approach with a total sampling technique involving 70 students. Data were collected using Likert-scale questionnaires and analyzed using Product Moment correlation and coefficient of determination. The results showed a correlation coefficient of 0.177 with a significance value of 0.142 (>0.05), indicating that there is no significant relationship between the school environment and students’ disciplinary behavior. The coefficient of determination revealed that the school environment contributed 3.1% to students’ disciplinary behavior, while 96.9% was influenced by other factors. These findings imply that although the school environment plays a role, disciplinary behavior is more dominantly shaped by internal and external factors beyond the school setting.